The Effects of Gonorrhea on Women's Reproductive Health - Wedha , Yoga Prawira; Azhalea, Diaz; Nuriasti, Rovera; Prudena, Balqis; Rafly, Muhammad; Qoriatul , Nanggi; Ary, Rizky; Sabrina, Yasmin; Regina, Anak Agung Ayu; Brilliant , Cantika; Tahriani, Ridha (Jurnal Biologi Tropis, 2025)
Neisseria gonorrhoeae is the bacteria that causes gonorrhea, a sexually transmitted infection (STI). The reproductive system, rectum, and pharynx are particularly susceptible to this infection. Both men and women can have gonorrhea, but women frequently have moderate or even nonexistent symptoms, which makes the infection go undiagnosed and untreated. This raises the possibility of severe side effects like infertility, pelvic inflammatory disease (PID), and transmission to fetuses or infants. According to a World Health Organization (WHO) assessment, gonorrhea is still a common global health issue, particularly in underdeveloped nations. Factors such as low awareness of STIs, limited access to health services, and increasing antibiotic resistance contribute to the challenges of controlling this disease. Throughout the twentieth century, gonorrhea (GO) was the most prevalent sexually transmitted infection (STI) globally due to delayed diagnosis. Gonorrhea was more common in women than in men in 2009, and the most common sources of reporting for women were emergency rooms (5.8%), STI clinics (16.7%), family planning clinics (9.1%), and other health department clinics (8.1%). Other sources of reporting were private physicians and health maintenance organizations (30.9%). According to WHO figures from 2012, there were 78 million GO infection cases. The frequency was 0.8% for women and 0.6% for males among those aged 15 to 49. According to WHO estimates from 2016, the combined global prevalence of urogenital gonorrhea (the percentage of the world's population that has gonorrhea in a given year) was 0.9% for women and 0.7% for men, or 30.6 million cases globally.